Analisis Budaya Patriarki pada Film Layar Lebar Yuni - Fenika Fenika; Suzy Azeharie (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
This research seeks to reveal the patriarchal cultural hegemony in Yuni's film. The film, which was released on December 9, 2021, uses Jaseng (Javanese Attack) dialogue with a duration of 122 minutes. The writer is interested in bringing up Yuni's film because in this film it depicts the culture of patriarchal hegemony. The purpose of this study is to determine the hegemony of patriarchal culture by using Tzvetan Todorov's narrative analysis which analyzes starting from the initial plot, the middle channel to the final plot. This study uses a qualitative approach with documentation techniques, namely collecting footage from Yuni's film and noting important parts of Yuni's film. In the initial flow it is described that the situation is still fine, the students go to school calmly without any problems. In the next scene, the middle plot is described, namely starting from an imbalance with the appearance of the first application to the third application from three different men to Yuni who does not want to get married and still wants to continue her education as high as possible. The final plot depicts Yuni running away from home and feeling free. This film depicts various forms of patriarchal hegemony, gender inequality and makes women subordinate compared to men who place women only as a means of reproduction. Men's will is considered much stronger, even women are seen as not having the right to voice their opinions. Penelitian ini berusaha mengungkap hegemoni budaya patriarki pada film Yuni. Film yang dirilis pada tanggal 9 Desember 2021 dialognya menggunakan Bahasa Jaseng (Jawa Serang) berdurasi 122 menit. Penulis tertarik mengangkat film Yuni karena dalam film ini menggambarkan budaya hegemoni patriarki. Penelitian ini menggunakan pendekatan kualitatif dengan teknik dokumenter yaitu. mengumpulkan materi dari film Yuni dan mencatat bagian-bagian yang sangat penting dari film Yuni. Pada aliran pertama digambarkan bahwa keadaan sekeliling Yuni masih baik, para siswa berangkat sekolah dengan tenang tanpa kendala. Adegan berikut menggambarkan plot tengah, yang dimulai dengan ketidakseimbangan ketika lamaran pertama untuk lamaran ketiga dari tiga pria berbeda muncul untuk Yuni, yang tidak ingin menikah dan masih ingin melanjutkan studinya semaksimal mungkin. Plot terakhir menunjukkan Yuni melarikan diri dari rumah dengan perasaan bebas. Film tersebut menggambarkan berbagai bentuk hegemoni patriarki, ketidaksetaraan gender dan subordinasi perempuan terhadap laki-laki yang memandang perempuan hanya sebagai alat reproduksi. Kehendak laki-laki dianggap jauh lebih kuat, perempuan juga tidak diperbolehkan untuk mengutarakan pendapatnya.